Annual Population Dynamics and Their Influencing Factors for an Endangered Submerged Macrophyte (Ottelia cordata) - Shen, Yichun; Lei, Jinrui; Song, Xiqiang; Ren, Mingxun (Frontiers in Ecology and Evolution, 2021)
Due to wetland destruction, Ottelia cordata (Wallich) Dandy had been categorized endangered species in the List of Key Protected Wild Plants in China. Quantifying the relative importance of biological traits that were related to demographic traits(growth, survival and reproduction) and water depth on population dynamic (abundance) of O. cordata could guide how to develop the best recovery strategies, but no studies had been done. By monitoring monthly changes of O. cordata in abundance and biological traits (plant height, leaf area, flower sex ratio, and seed number) that were highly correlated with growth rate, photosynthetic rate, and water depth, relationships of them were obtained. Linear mixed effect models and variance partition quantified the specific effects of four biological traits and water depth on O. cordata abundance in three habitat types (paddyfield, stream and spring). The linear mixed effect models results that among the four biological traits, height could be significantly positively correlated to abundance in all three habitat types, but other three traits (leaf area, sex ratio and seed numbers) were non-significantly associated with abundance. The height was determined by water depth, so water depth rather than photosynthetic rate and reproduction rate could promote the development and reconstruction of O. Cordata population. However, variance partition results showed that water depth mediated the positive influence of growth rate on abundance of O. cordata in paddyfield and spring. In contrast, water depth but not growth rate determined abundance of O. cordata in stream. However, water depth had a high negative limited on the abundance in stream habitats. Thus, one urgent recovering strategy could be deduced, namely, in the short term for avoiding the potential harm or even extinction of O. cordata, keeping appropriate water depth or transplanting O. cordata to spring should be a effective strategy. In addition, the turbidity of water body would affect the density of O. cordata growth,when turbidity was high, O. cordata was sparsely distributed. Therefore, in the long run, in order to make the population recover, it was necessary to restore the degraded wetland, such as reducing water pollution and removing sludge to keep the water clean.